2013
DOI: 10.1371/journal.pone.0075768
|View full text |Cite
|
Sign up to set email alerts
|

Too Good to Be True: Rhesus Monkeys React Negatively to Better-than-Expected Offers

Abstract: To succeed in a dynamically changing world, animals need to predict their environments. Humans, in fact, exhibit such a strong desire for consistency that one of the most well-established findings in social psychology is the effort people make to maintain consistency among their beliefs, attitudes, and behavior. However, displeasure with unpredictability leads to a potential paradox, because a positive outcome that exceeds one’s expectations often leads to increased subjective value and positive affect, not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…To better understand the influence of attention and memory on decision-making dynamics, we examined free-choice sequences of multi-option, multi-attribute decisions in rhesus monkeys as they compared different food items in view. Rhesus monkeys are a representative catarrhine primate (comprising Old World monkeys, apes, and humans) whose findings contribute to our understanding of the evolutionary origins of decision-making processes; they are also well-established as a non-human primate model of human decision making (Glimcher et al, 2008; Platt and Ghazanfar, 2010; Xu et al, 2011; Kralik et al, 2012; Jung and Kralik, 2013; Knight et al, 2013). In particular, we addressed the question of how selective attention and memory relate to the two key components of sequential decision making: preference bias, i.e., the overall choice distribution, and choice persistence, i.e., the tendency to repeat choices.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the influence of attention and memory on decision-making dynamics, we examined free-choice sequences of multi-option, multi-attribute decisions in rhesus monkeys as they compared different food items in view. Rhesus monkeys are a representative catarrhine primate (comprising Old World monkeys, apes, and humans) whose findings contribute to our understanding of the evolutionary origins of decision-making processes; they are also well-established as a non-human primate model of human decision making (Glimcher et al, 2008; Platt and Ghazanfar, 2010; Xu et al, 2011; Kralik et al, 2012; Jung and Kralik, 2013; Knight et al, 2013). In particular, we addressed the question of how selective attention and memory relate to the two key components of sequential decision making: preference bias, i.e., the overall choice distribution, and choice persistence, i.e., the tendency to repeat choices.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental human and monkey studies have shown that surprising events or outcomes harm individuals, even when the error is positive (Knight et al, 2013;Topolinski and Strack, 2015). Topolinski and Strack (2015) used facial electromyography to measure people's responses immediately after surprising information; they observed that participants flexed their corrugator muscles, which indicated negative valence.…”
Section: Introductionmentioning
confidence: 99%
“…Topolinski and Strack (2015) used facial electromyography to measure people's responses immediately after surprising information; they observed that participants flexed their corrugator muscles, which indicated negative valence. Knight et al (2013) showed that in a predictable food-taking paradigm, rhesus monkeys were slower to accept unexpected offers and exhibited aversive reactions, such as repeatedly turning their heads and looking away before accepting the food item, especially in response to better-than-expected offers. These studies indicate that surprise decreases, at least initially, the value of an event for individuals and decreases the value of the offer associated with the event.…”
Section: Introductionmentioning
confidence: 99%
“…Recent human and monkey experimental studies have shown that surprisal events or outcomes have a negative impact on individuals, even when the error is positive [4,5]. Topolinski and Strack [5] employed facial electromyography to measure people's responses immediately following surprising information; they observed that participants flexed their corrugator muscles, corresponding to a furrowing of the eyebrows, which indicated negative valence.…”
Section: Introductionmentioning
confidence: 99%
“…Topolinski and Strack [5] employed facial electromyography to measure people's responses immediately following surprising information; they observed that participants flexed their corrugator muscles, corresponding to a furrowing of the eyebrows, which indicated negative valence. Knight et al [4] showed that, in a predictable food taking paradigm, rhesus monkeys were slower to accept unexpected offers and exhibited aversive reactions such as repeatedly turning their heads and looking away before accepting the food item, especially in response to better-than-expected offers. These studies indicate that surprise decreases, at least initially, the value of an event for individuals, and decreases the value of the offer associated with the event.…”
Section: Introductionmentioning
confidence: 99%